39 Ministernotomy for aortic valve replacement- is it safe and effective?. (28th September 2016) - Ryan, E; Bargenda, S; El-Tayeb, N; Hurley, J; McCarthy, J
Abstract : Background: Surgical aortic valve replacement has been shown to be an extremely safe and effective operation. In order to reduce patient morbidity, we recently commenced a ministernotomy approach to the aortic valve. Methods: Between 2012 and the present 90 aortic valve replacements have been performed using this less invasive technique. Age ranged from 33 to 87 years. The technique involved partial sternotomy of 7–8 cm with a 'J' to the left. Cardiopulmonary bypass was established with low profile cannulae, and the replacement of the aortic valve proceeded with a standard surgical technique in 82 patients and with a sutureless rapid deployment valve in 6 patients. Results: 30 day mortality was 0%, 4 patients required conversion to full sternotomy. One patient had reoperation for bleeding post surgery. All patients were discharged well. Conclusions: Aortic valve replacement via a ministernotomy is a safe and effective procedure.